Database resources of the National Center for Biotechnology Information in 2023. Issue Volume 51:Issue D1(2023) (12th November 2022) - Sayers, Eric W; Bolton, Evan E; Brister, J Rodney; Canese, Kathi; Chan, Jessica; Comeau, Donald C; Farrell, Catherine M; Feldgarden, Michael; Fine, Anna M; Funk, Kathryn; Hatcher, Eneida; Kannan, Sivakumar; et al.
Abstract: The National Center for Biotechnology Information (NCBI) provides online information resources for biology, including the GenBank® nucleic acid sequence database and the PubMed® database of citations and abstracts published in life science journals. NCBI provides search and retrieval operations for most of these data from 35 distinct databases. The E-utilities serve as the programming interface for most of these databases. New resources include the Comparative Genome Resource (CGR) and the BLAST ClusteredNR database. Resources receiving significant updates in the past year include PubMed, PMC, Bookshelf, IgBLAST, GDV, RefSeq, NCBI Virus, GenBank type assemblies, iCn3D, ClinVar, GTR, dbGaP, ALFA, ClinicalTrials.gov, Pathogen Detection, antimicrobial resistance resources, and PubChem. These resources can be accessed through the NCBI home page at https://www.ncbi.nlm.nih.gov .